2009
DOI: 10.1177/0272989x09349961
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Modified Rankin Scale (mRS) Measurement into the Generic EuroQol (EQ-5D) Health Outcome

Abstract: The choice of algorithm will be dependent on the study aim. Individuals outside the United Kingdom may find it more useful to use the multinomial results, which can be used with different country-specific tariff valuations. However, these algorithms should not replace prospective collection of utility data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
118
2
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(128 citation statements)
references
References 23 publications
3
118
2
3
Order By: Relevance
“…130 Despite the difficulties, 131 a mapping of the OHS into the EQ-5D QALY suggests that each point in the OHS is worth 0.0222 of a QALY. 132 A change of 20 points in the OHS, the mean value in the PROMs 2008-12 data set, would then correspond to 0.444 of a QALY (compare the actual QALY change of 0.411).…”
Section: Prioritising Patients For Elective Surgery: the Efficiency Omentioning
confidence: 99%
“…130 Despite the difficulties, 131 a mapping of the OHS into the EQ-5D QALY suggests that each point in the OHS is worth 0.0222 of a QALY. 132 A change of 20 points in the OHS, the mean value in the PROMs 2008-12 data set, would then correspond to 0.444 of a QALY (compare the actual QALY change of 0.411).…”
Section: Prioritising Patients For Elective Surgery: the Efficiency Omentioning
confidence: 99%
“…The cost of asthma exacerbations represented a mixture of the estimated cost of an accident and emergency (A&E) attendance and NHS reference cost of inpatient attendance, with the ratio of A&E to inpatient admissions estimate taken from Hoskins et al 84 Costs for stroke were taken from a recent National Institute for Health Research (NIHR) commissioned technology assessment report, 98 and incorporates the one-off and ongoing costs of stroke in addition to the reported difference in costs and prevalence of dependent and independent patient states following a stroke incident. 99 All costs have been adjusted for inflation to 2010/11 prices. 100 Uncertainty around cost estimates were incorporated into the probabilistic analysis.…”
Section: Costsmentioning
confidence: 99%
“…The outcome following a stroke is estimated using a two-stage process, using data from Rivero-Arias et al 154 This paper 154 reported that, of 1283 patients who had a stroke within the Oxford Vascular Study (OXVASC) cohort, 24.8% (319/1283) were dead within 24 months. Of those who survived, the degree of disability following the stroke was graded according to the modified Rankin Scale (mRS) 24 months after the event in 425 patients.…”
Section: Determining the Category Of Strokementioning
confidence: 99%
“…154 Utility multipliers following a stroke were estimated from data that presented EuroQOL Five Dimension (EQ-5D) mapped utility estimates for the utility associated with each of the six mRS scores. As the mildest of these categories (mRS 0) is a full recovery, this is assumed to represent baseline patient utility.…”
Section: Determining the Category Of Strokementioning
confidence: 99%
See 1 more Smart Citation